Customer responsive management : the flexible advantage - Davis, Frank W. (Frank White), 1939-; Mandrodt, Karl B. (Cambridge, MA : Blackwell, 1996)
This book is about: An introduction to customer responsiveness; The evolving economic focus; The customer-responsive model; The customer relationship management task; ...
Keywords: Management; Customer services; Customer services -- Management; Consumer satisfaction